2003
DOI: 10.1002/ijc.11444
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of breast cancer resistance protein–mediated drug resistance by tryprostatin A

Abstract: MDR in human cancers is one of the major causes of failure of chemotherapy. A member of the superfamily of ABC transporters, BCRP, was demonstrated to confer an atypical MDR phenotype to tumor cells. To overcome the BCRPmediated drug resistance, the fungal secondary metabolite TPS-A, a diketopiperazine, was analyzed with regard to its potency to reverse the BCRP-mediated drug-resistant phenotype. At concentrations of 10 -50 M, TPS-A reversed a mitoxantrone-resistant phenotype and inhibited the cellular BCRP-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 30 publications
1
60
1
1
Order By: Relevance
“…Hoechst 33342 dye efflux activity was also inhibited by a novel ABCG2 inhibitor, TPS-A (Fig. 2B), that is known not to inhibit another important ATP-binding cassette transporter, P-glycoprotein [23]. These data strongly suggest that ABCG2 is a major contributor to the SP phenotype of limbal epithelial cells.…”
Section: Effect Of 5d3 and Tps-a On Hoechst 33342 Dye Effluxmentioning
confidence: 80%
See 1 more Smart Citation
“…Hoechst 33342 dye efflux activity was also inhibited by a novel ABCG2 inhibitor, TPS-A (Fig. 2B), that is known not to inhibit another important ATP-binding cassette transporter, P-glycoprotein [23]. These data strongly suggest that ABCG2 is a major contributor to the SP phenotype of limbal epithelial cells.…”
Section: Effect Of 5d3 and Tps-a On Hoechst 33342 Dye Effluxmentioning
confidence: 80%
“…Though verapamil is generally used to identify the SP phenotype in the Hoechst 33342 dye exclusion assay, it is insufficient in specificity to demonstrate the contribution of ABCG2 to the SP phenotype of limbal epithelial cells. As ABCG2-specific inhibitors, fumitremorgin C [33], 5D3 monoclonal antibody [13,22], and TPS-A [23] are reported. Our SP analysis of limbal epithelial cells using 5D3 and TPS-A showed that both 5D3 and TPS-A effectively inhibit Hoechst 33342 dye efflux from these cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other notable BCRP inhibitors include, among others, novobiocin (54), tamoxifen, and its derivatives TAG-11 and TAG-139 (56), reserpine (57), the pipecolinate derivatives VX-710 (Biricodar) (61), tryprostatin A (a A. fumigatus second metabolite) (62), and dietary flavonoids such as chrysin and biochanin A (63).…”
Section: Bcrp Inhibitorsmentioning
confidence: 99%
“…FTC, temel farmakoloji çalış-malarında oldukça sık kullanılmasına rağmen nörotoksik etkileri nedeniyle klinikte kullanılmamaktadır. FTC'nin yanı sıra Ko 143, triprostatin A (TPS-A) ve silimarin, hesperetin, kuersetin ve daidzein gibi flavonoidler, siklosporin A, elakridar ve tarikidarın da BCRP'yi inhibe ettiği yapılan çeşitli çalışmalarla gösterilmiştir (74)(75)(76)(77)(78).…”
Section: Bcrp (Abcg2 Meme Kanseri Direnç Proteini)unclassified